Fibro Adipose Vascular Anomaly: A Rare and Often Misdiagnosed Entity - Khera, Pushpinder S.; Garg, Pawan K.; Babu, Santhosh; Elhence, Poonam; Tiwari, Sarbesh; NK, Shyamkumar (Indian Journal of Radiology and Imaging, 2021)
Fibro adipose vascular anomaly (FAVA) is a rare type of vascular malformation with distinct clinical features. The authors here discussed the clinical, imaging, differential diagnosis, histopathological features, and treatment options of FAVA along with an illustrative case. It is important to know about this uncommon entity as this can be misdiagnosed due to the overlapping clinical features with other common entities. It is a benign condition with no proven malignant potential. There are no guidelines regarding the best treatment option.
Keywords: fibro adipose vascular anomaly; vascular malformation; venous malformation